Analisis Volatilitas dan Forecasting Inflasi di Indonesia - Salimah, Nur Syawaliyah; Satrianto, Alpon (Jurnal Kajian Ekonomi dan Pembangunan, 2025)
This study aims to analyze the volatility of inflation based on expenditure groups and forecasting the inflation rate using ARIMA and ARCH/GARCH methods. The data used is monthly inflation data from January 2006 to November 2024 obtained from the Central Statistics Agency (BPS). The analysis shows that inflation volatility varies across expenditure groups, with major factors such as changes in energy and food prices. The ARIMA model good results in forecasting inflation, while the ARCH/GARCH model is used to identify and analyze significant inflation volatility. This research contributes to economic policy making, especially in maintaining price stability and formulating effective policies to reduce the negative impact of inflation on society. The findings are expected to serve as a basis for future monetary and fiscal policy planning.